ART STRUCTURE OF THE THEMATIC FEMALE IMAGE ACCORDING TO FOLKLORE MOTIVES: STAGES OF CREATION - Шаркіна, А. Г. (Art and Design, 2020)
The aim of the article. The aims of the article are to provide the integrated study of the art structure features of the thematic image development for cultural events by means of makeup, costume, additions; to determine the specifics of the make-up artist vision influence on the image character; its correspondence to the general concept of the event.Historical method, analytical method and comparative analysis method have been used in the pre-project research. The art-associative method, which provided the combination of the female image from the Slavic mythology calendar rites with the modern vision of fashion and female canons of beauty, has been used in the research project process. The sequence of a thematic image creation process for the event with competitional and concert program has been highlighted in the article. The image creation process can be implemented in three stages: the search for an idea and the thematic female image conceptual content definition; the expression means search and necessary materials preparation; the stylization and realization of the image. The importance of external associations, that arises, according to the concept of the event, as a reflection in minds of historical folklore heritage about the autumn calendar cycle customs and rites, on the stage of the image idea search have been determined. The project idea is to embody the interaction of a young, direct perception of the world by a young girl with the cultural experience of ancient Ukrainians and is implemented on the principle of using contrasts – shape, color and texture. The thematic image of the event has been formed with the help of associations with ancient Slavic mythology female images. The scientific novelty is in the definition of the concept, design methods and means of thematic female image development based on the appeal to the ancient Ukrainian cultural heritage. The art-associative method has been identified as the most effective method for the folklore motives based image formation. The art structure of the thematic female image for the cultural event has been revealed; the modern author vision in the expression means selection has been actualized. The sequences of thematic female image development for the cultural and art event, which embodies the concept of the event and perform the strengthening function of the impression and influence on visitors, have been represented. Three stages of project implementation from the conception stage to realization stage have been stated and implemented.